AM1 and PM3 Studies in Corrosion of Mild Steel in Presence of Aniline and its Derivatives - Tandon, H.C.; Kumar, Sanjay; Singh, Laxman (Asian Journal of Chemistry, 2010)
The effect of aniline and its derivatives o-nitroaniline, p-nitroaniline, o-toluidine, p-toluidine, o-chloroaniline and p- ehloroaniline on the corrosion of mild steel in concentrated sulphuric acid has been investigated theoretically. The calculations are done by using semi-empirical methods like Austin Model 1 (AM1) and Parametric Method-3 (PM3) to study the effectiveness of these compounds as inhibitors. The present work shows similar observations to those that have been reported experimentally. The results have been discussed on the basis of dipole moments, heats of formation and net atomic charge on the N-atom of the compounds.